Edinburgh DataShare - A DSpace Data Repository: Achievements and Aspirations - Macdonald, Stuart (Presented at the Fedora-UK&I&EU Meeting, Oxford, 2009)
An overview of the evolution of an institutional data repository, Edinburgh DataShare
Keywords: research data; institutional repository; data repository